Effects of operational shocks on key microbial populations for biogas production in UASB (Upflow Anaerobic Sludge Blanket) reactors - Couras, C. S.
This work compares the overall performance and biogas production of continuous and intermittent UASB (Upflow Anaerobic Sludge Blanket) reactors treating dairy wastewater and subjected to fat, hydraulic and temperature shocks. The systems were monitored for methane production, effluent concentration, volatile fatty acids, and microbial populations of the Eubacteria, Archaea and Syntrophomonadaceae groups. This last microbial group has been reported in literature as being determinant for the degradation of fatty substrates present in the wastewater and subsequent biogas production. Results show that both continuous and intermittent systems supported the applied shocks. However, the intermittent systems exhibited better performance than the continuous systems in biogas production and physical-chemical parameters. Syntrophomonadaceae microbial group was present in the intermittent systems, but was not detected in the biomass from the continuous systems. Hydraulic and temperature shocks, but not the fat shock, caused severe losses in the relative abundance of the Syntrophomonadaceae group in intermittent systems, leading to undetectable levels during the temperature shock. The severity of the effects of the applied shocks on the key microbial group Syntrophomonadaceae, were classified as: fats < hydraulic < temperature. Results from a full-scale anaerobic reactor confirm the effect of intermittent operation on the presence of Syntrophomonadaceae and the effect on reactor performance.